Antibiotic prescribing in relation to diagnoses and consultation rates in Belgium, the Netherlands and Sweden: use of European quality indicators. (2nd January 2017) - Tyrstrup, Mia; van der Velden, Alike; Engstrom, Sven; Goderis, Geert; Molstad, Sigvard; Verheij, Theo; Coenen, Samuel; Adriaenssens, Niels
Abstract: Objective: To assess the quality of antibiotic prescribing in primary care in Belgium, the Netherlands and Sweden using European disease-specific antibiotic prescribing quality indicators (APQI) and taking into account the threshold to consult and national guidelines. Design: A retrospective observational database study. Setting: Routine primary health care registration networks in Belgium, the Netherlands and Sweden. Subjects: All consultations for one of seven acute infections [upper respiratory tract infection (URTI), sinusitis, tonsillitis, otitis media, bronchitis, pneumonia and cystitis] and the antibiotic prescriptions in 2012 corresponding to these diagnoses. Main outcome measures: Consultation incidences for these diagnoses and APQI values (a) the percentages of patients receiving an antibiotic per diagnosis, (b) the percentages prescribed first-choice antibiotics and (c) the percentages prescribed quinolones. Results: The consultation incidence for respiratory tract infection was much higher in Belgium than in the Netherlands and Sweden. Most of the prescribing percentage indicators (a) were outside the recommended ranges, with Belgium deviating the most for URTI and bronchitis, Sweden for tonsillitis and the Netherlands for cystitis. The Netherlands and Sweden prescribed the recommended antibiotics (b) to a higher degree and the prescribing of quinolones exceeded the proposed range for most diagnoses (c) in Belgium. The interpretation of APQI was found to be dependent on the consultation incidences. High consultation incidences were associated with high antibiotic prescription rates. Taking into account the recommended treatments from national guidelines improved the results of the APQI values for sinusitis in the Netherlands and cystitis in Sweden. Conclusion: Quality assessment using European disease-specific APQI was feasible and their inter-country comparison can identify opportunities for quality improvement. Their interpretation, however, should take consultation incidences and national guidelines into account. Differences in registration quality might limit the comparison of diagnosis-linked data between countries, especially for conditions such as cystitis where patients do not always see a clinician before treatment. Key points: The large variation in antibiotic use between European countries points towards quality differences in prescribing in primary care. The European disease-specific antibiotic prescribing quality indicators (APQI) provide insight into antibiotic prescribing, but need further development, taking into account consultation incidences and country-specific guidelines. The incidence of consultations for respiratory tract infections was almost twice as high in Belgium compared to the Netherlands and Sweden. Comparison between countries of diagnosis-linked data were complicated by differences in data collection, especially for urinary tract infections.